Essay on the Beethoven Week in Vienna in Dec. 1870 by August Silberstein from Über Land & Meer - Silberstein, August (author):::Creator:::::::::::: (Stuttgart; Germany; Eduard Hallberger, 2020)
Article by August Silberstein on the Beethoven Week activities in Vienna in December 1870 in celebration of the 100th anniversary of Beethoven's birth.